Desenvolvimento ovariano do Prochilodus lineatus em dois sistemas de produção: tanques rede e viveiros escavados - Hainfellner, Patrick [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
O desenvolvimento de técnicas para indução à reprodução de peixes migradores (espécies reofílicas) de água doce possibilitou uma produção consistente de larvas destas espécies, embora, seja comum deparar-se com relatos de produtores sobre fêmeas que não ovulam adequadamente ou simplesmente não ovulam após os procedimentos de desova induzida. Algumas evidências sugerem que a origem deste problema pode estar ligada ao manejo inapropriado das matrizes. Infelizmente pouco se sabe sobre o manejo correto de reprodutores de peixes reofílicos em cativeiro. Deste modo, a proposta deste estudo foi avaliar comparativamente o processo de desenvolvimento ovocitário de reprodutores de Prochilodus lineatus mantidos em dois sistemas de criação: viveiros escavados (VE) e tanques rede (TR), seguindo as densidades de 1 peixe.m2 e 17 peixes.m3 respectivamente. A escolha do TR se deu por ser um sistema que simula experimentalmente muitas das condições inapropriadas de manejo empregadas em diversas pisciculturas, tais como: elevadas densidades de estocagem e água de má qualidade. A cada dois meses foram feitas amostragens de 30 animais de cada tratamento, de onde 5 fêmeas foram escolhidas ao acaso e sacrificadas para remoção das gônadas, fígado e vísceras para determinação dos índices gonado (IGS), hepato e viscero-somático, fator K, e para as análises histomorfométricas dos ovários. Amostras de sangue foram coletadas para a determinação da variação anual dos níveis de esteróides gonadais (estradiol e 17-alfa-hidroxiprogesterona)...

The development of techniques of induced breeding of South American migratory fresh water fish (rheophilic species) has enabled a consistent production of fingerlings of these species, however nowadays it is very common to come across reports of fingerling producers about females that do not ovulate properly or just do not ovulate. In this context, some evidences suggest that the origin of such problem may be an inappropriate broodstock management. Unfortunately few is known about the proper management of migratory breeders in captivity, thus the main purpose of this study was to evaluate, comparatively, the process of oocyte production in Prochilodus lineatus breeders kept into two distinct production systems: earthen ponds (EP) and cages (C), with the following stocking densities 1fish.m2 and 17fish.m3 respectively. The reasons for the choice of C was because this system shares a number of inappropriate characteristics employed in diverse fish farms, such as high stocking densities and poor water quality. Every two months thirty specimens of one of the EP and C unities were randomly collected for biometric analysis. After that, five specimens of each treatment were randomly chosen to be sacrificed for removal of gonads, liver and viscera for determination of gonadosomatic index (GSI), hepato-and viscero-somatic indexes, K factor, and also for the histomorphometric analysis of the ovaries. Blood samples were also collected for determining the annual variation in plasma gonadal steroids levels (stradiol and 17 alpha-hydroxyprogesterone).The results showed that the process of ovarian maturation is completely compromised in females kept in C, with significant 30 reduction in the volume of vitellogenic oocytes, estradiol, hydroxyprogesterone, and consequently in the GSI values. Besides the reproductive period is shortened and starts late in relation to that of females of VE... (Complete abstract click electronic access below)
Keywords: Peixe - Criação; Reprodução; Desenvolvimento ovocitário; Peixes reofilicos; Prochilodys lineatus; Rheophilic fish; Oocyte development; Gonadal steroides; Production system; Reproduction